Teh dalam Jamuan Kenegaraan Ala Keraton Yogyakarta sebagai Gastrodiplomasi - Lutfi Maulana Hakim; Erwita Danu Gondohutami (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
As one of the most well-known types of drink throughout the world, it is not surprising that the presence of tea in Yogyakarta Palace is high. Tea is always served in the Sultan and family's private dishes, traditional ceremonies, and state banquets. In other countries, tea has even become an identity and a diplomatic tool. Seeing this phenomenon, this research was created to dig deeper into the existence of tea in the Yogyakarta Palace, especially at state banquets and its relation to a form of culinary diplomacy known as gastrodiplomacy. In this qualitative research, it was found that tea was always served as choice of drink at state banquets. However, until now there has not been a special format or procedure for a tea party to entertain state guests. It would be interesting if in the future the palace could develop a Yogyakarta Palace style tea reception in order to maximize the potential for gastrodiplomacy which could have various positive implications for collaboration in various needed sectors.